The Influence of Occupational Health and Safety and the Work Environment on Worker Productivity - Rosita K, Dhea; Intan A, Syabikah; Alfatun J, Moch; Rozy, Nikko (Syntax Corporation Indonesia, 2024)
Occupational safety and health are very fundamental for companies, because the impact of work accidents is not only detrimental to workers, but also the company. The aim of this research is to determine how much influence Occupational Safety and Health and the Work Environment influence Worker Productivity. This research uses primary data, namely a questionnaire distributed to 55 PT Arteria Daya Mulya Cirebon. Data analysis methods use Instrument Tests including Validity Tests, Reliability Tests, Classical Assumption Tests including Normality Tests, Multicollinearity Tests, Regression Analysis Tests including Multiple Linear Regression Analysis, Determination Coefficients, and Hypothesis Tests including T Tests (partial) and F Tests (simultaneous) which was processed using the IBM SPSS version 23.0 for Windows application. The research results show that Occupational Health and Safety has a significant effect of 0.000 < 0.05 and the calculated t value > t table (9.991 > 0.1674), meaning that Ho is rejected and Ha is accepted. So it can be concluded that occupational health and safety variables have a positive and significant effect on worker productivity. Then the Work Environment has a positive and significant effect on Worker Productivity with a significance value of 0.000 < 0.05 and a calculated t value > t table (11.735 > 1.674), meaning that Ho is rejected and Ha is accepted. So it can be concluded that the Work Environment variable has a positive and significant effect on Worker Productivity. Occupational Health and Safety and the Work Environment together (simultaneously) have a significant positive effect on Worker Productivity as seen from the significance value of 0.000 < 0.05 and the calculated f value > f table (82.690 > 3.17), meaning that Ho is rejected and Ha accepted. So it can be concluded that the Occupational Health and Safety and Work Environment variables together have a positive and significant influence on Worker Productivity with an adjusted R square value of 76.1%.